The Effect of Beta Cyclodextrin on the Removal of Cholesterol from Buffalo Milk - Mudassir, Zunnurain; Nadeem, Muhammad; Baig, Hafiza Anam (Biological Sciences - PJSIR, 2017)
This study was conducted to find out the efficiency of beta cyclodextrin (bCD) for the removal of cholesterol from buffalo milk. Standardised (3.5% fat) and homogenised buffalo milk was treated with bCD at three different concentrations i.e., 0.5, 1 and 1.5% (T1, T2 and T3) and compared with a control without bCD treatment. Treatment of milk with bCD at all concentrations did not show any negative impact on pH and acidity of milk. 90% cholesterol was removed when buffalo milk was treated with 1.5% bCD. Treatment of milk with bCD did not reveal significant effect on fatty acid and triglyceride composition of milk as well as physicochemical and sensory characteristics (P>0.05). These results depicted that bCD can be used efficiently for the removal of cholesterol from buffalo milk.